Thermodynamic behavior of pyrimidine derivatives on multilayer Fe crystal structure: Molecular dynamics and surface layer interaction - Ghadah H. Alwan; Maysaa A. Mohammed; Muntadher H. Al-Ameri; Amira A. Abduljaleel; Safa H. Mohammed; Hasan R. Obayes; Doaa S. El Sayed; Ali Abdullah Issa (Chemical Thermodynamics and Thermal Analysis)
This study aimed to evaluate the structural, electronic, and adsorption behavior of a series of O- and S-pyrimidine derivatives, substituted with NO₂, Cl, Br, and OH groups, as potential inhibitors on a designed multilayered Fe surface. A comprehensive computational approach was employed, including geometry optimization, frontier molecular orbital (FMO) and molecular electrostatic potential (MEP) analyses, thermodynamic calculations, molecular dynamics simulations, and Monte Carlo-based adsorption modeling. Structural optimization and packing morphology analysis were performed for Pyr 1 and Pyr 2 to assess how substituent variations influence polymorph formation and surface packing behavior on the Fe lattice. FMO and MEP results identified key active sites and indicated good system stability, particularly for Pyr 3 and Pyr 7. Thermodynamic data showed minor stability variations based on substituent type, while molecular dynamics simulations highlighted strong surface interactions for Pyr 1, Pyr 3, Pyr 5, and Pyr 7. The adsorption locator study confirmed effective adsorption and conformational adaptability of the inhibitors on the Fe surface, influenced by the nature of the substituent groups. These findings provide a theoretical foundation for the design of pyrimidine-based inhibitors targeting metal surfaces.